A dynamic beam switching metasurface based on angular mode-hopping effect - Hu, Dongyu; He, Shaowei; Li, Shibin; Zhu, Weiming (Frontiers in Physics, 2024)
Fast and versatile beam forming and steering technologies are now crucial for various emerging applications, including wireless optical communications and optical switches. However, these technologies often rely on expensive components, such as spatial light modulators (SLMs) and optical phase arrays (OPAs), which come with complex and power-consuming control systems. In response to this challenge, we propose a dynamic beam-switching method inspired by the mode-hopping effect of lasers. As a proof of concept, we introduce the dynamic beam switching metasurface (DBSM) design, featuring an in-plane mechanical actuation system. Our numerical analyses, based on the finite element method (FEM), demonstrate that the proposed DBSM exhibits versatile beam forming and steering functionalities. These include beam splitting and omnidirectional beam steering. Moreover, we anticipate that the tuning speed of the DBSM will reach the kilohertz (kHz) range or even higher when utilizing a microelectromechanical systems (MEMS) actuator, building upon pioneering research in this field. We envision it holds promising applications in areas such as light detection and ranging (LiDAR), optical wireless communication devices, and optical switches.